Adverse Pregnancy Outcomes and Chronic Hypertension in the Era of Prevention: A Contemporary, Retrospective Cohort Study Using Data from the National Inpatient Sample Database - Stairs, Jocelyn; Nash, Christopher M.; Rolnik, Daniel L. (American Journal of Perinatology, 2024)
Chronic hypertension is a known risk factor for the development of preeclampsia and obstetrical morbidity. However, recent risk estimates, particularly in the era of use of low-dose acetylsalicylic acid for preeclampsia prevention, are lacking. This study aimed to estimate the association between chronic hypertension and preeclampsia and other adverse pregnancy outcomes in a contemporary cohort of births spanning the period, since the introduction of a low-dose acetylsalicylic acid protocol. The secondary outcome was to estimate trends in preeclampsia and preterm birth among patients with chronic hypertension during the study period.A retrospective, population-based cohort study was conducted using the National Inpatient Sample Database to identify individuals discharged from hospitals in the United States following obstetrical delivery from 2014 to 2019. Pregnancies complicated by chronic hypertension were identified using ICD 9/10 (International Classification of Diseases 9th and 10th editions) codes. Multivariable logistic regression models were used to estimate the adjusted odds ratios for the association between chronic hypertension and adverse pregnancy outcomes compared with pregnancies not complicated by chronic hypertension. Temporal trends in preeclampsia and preterm birth among patients with chronic hypertension were estimated over the study period.Among 4,451,667 obstetrical delivery-related admissions, 139,556 (3.1%) included pregnancies complicated by chronic hypertension. Of these, 27,146 (19.4%) admissions included pregnancies with superimposed preeclampsia, compared with 222,351 (5.2%) of admissions that included pregnancies with preeclampsia without prior diagnosis of chronic hypertension. Pregnancies complicated by chronic hypertension were associated with 3.29 times the odds of preeclampsia compared with pregnancies without chronic hypertension (95% confidence interval: 3.22–3.36), but the odds of preeclampsia (p-value for linear trend <0.0001) and preterm birth (p-value for linear trend = 0.0001) in this subgroup decreased over the study period.While the odds of preeclampsia are increased among pregnancies complicated by chronic hypertension, the odds of preeclampsia in this population have decreased over time.
Keywords: preeclampsia; chronic hypertension; preterm birth; acetylsalicylic acid; prevention; adverse pregnancy outcomes